Influence of the dental implant number and load direction on stress distribution in a 3-unit implant-supported fixed dental prosthesis - Silveira, Marcos Paulo Motta [UNESP]; Campaner, Larissa Mendes [UNESP]; Bottino, Marco Antonio [UNESP]; Nishioka, Renato Sussumu [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Tribst, João Paulo Mendes [UNESP] (Wroclaw Medical University, 2021)
Background. The choice between 2 or 3 implants to support a 3-unit implant-supported fixed dental prosthesis (FDP) still generates doubt in clinical practice. Objectives. The aim of this study was to evaluate stress distribution in 3-unit implant-supported FDPs according to the implant number and load direction. Material and methods. A numerical simulation was performed to analyze stress and strain according to the implant number (2 or 3) and load direction (axial or oblique). A model of a jaw was created by means of the modeling software Rhinoceros, v. 5.0 SR8. External hexagon implants, micro-conical abutments and screws were also modeled. The final geometries were exported to the computer-aided engineering (CAE) software Ansys, v. 17.2, and all materials were considered homogeneous, isotropic and elastic. Different load directions were applied for each model (300 N) at the center of the prosthesis. Results. The von Mises stress and strain values were obtained for the titanium structures and the bone, respectively. The implant number influenced the prosthesis biomechanics, with higher stress and strain concentrations when 2 implants were simulated. The oblique load also affected the mechanical response, showing higher stress and strain in comparison with the axial load, regardless of the implant number. Conclusions. It was concluded that for a 3-unit implant-supported FDP, a greater number of implants associated with axial loads can result in a better mechanical response during chewing.
Keywords: Biomechanics; Dental implants; Finite element analysis; Fixed dentures; Stress distribution